Treatment of Repeated Implantation Failures with Sequential Embryo Transfer to Achieve a Successful Pregnancy: A Case Report - Xia, Lingjin; Che, Qi; Liu, Miao; Lu, Xinmei; Cao, Xiang; Dong, Xi; Liu, Suying (Archives of Clinical and Biomedical Research, 2020)
To report a case with multiple embryo transfers failure. A 30-year-old woman, married for 10 years, has undergone five ovulation stimulation cycles, and eight transfers cycles without achieving clinical pregnancy. A successful pregnancy was obtained after day 2 cleavage stage embryo combined with the day 5 blastocyst transfer, and a healthy male infant was delivered at 39+3 weeks.